Artificial intelligence-based polyp size measurement in gastrointestinal endoscopy using the auxiliary waterjet as a reference - Sudarevic, Boban; Sodmann, Philipp; Kafetzis, Ioannis; Troya, Joel; Lux, Thomas J.; Saßmannshausen, Zita; Herlod, Katja; Schmidt, Stefan A.; Brand, Markus; Schöttker, Katrin; Zoller, Wolfram G.; Meining, Alexander; Hann, Alexander (Endoscopy, 2023)
Background Measurement of colorectal polyp size during endoscopy is mainly performed visually. In this work, we propose a novel polyp size measurement system (Poseidon) based on artificial intelligence (AI) using the auxiliary waterjet as a measurement reference.Methods Visual estimation, biopsy forceps-based estimation, and Poseidon were compared using a computed tomography colonography-based silicone model with 28 polyps of defined sizes. Four experienced gastroenterologists estimated polyp sizes visually and with biopsy forceps. Furthermore, the gastroenterologists recorded images of each polyp with the waterjet in proximity for the application of Poseidon. Additionally, Poseidon's measurements of 29 colorectal polyps during routine clinical practice were compared with visual estimates.Results In the silicone model, visual estimation had the largest median percentage error of 25.1 % (95 %CI 19.1 %–30.4 %), followed by biopsy forceps-based estimation: median 20.0 % (95 %CI 14.4 %–25.6 %). Poseidon gave a significantly lower median percentage error of 7.4 % (95 %CI 5.0 %–9.4 %) compared with other methods. During routine colonoscopies, Poseidon presented a significantly lower median percentage error (7.7 %, 95 %CI 6.1 %–9.3 %) than visual estimation (22.1 %, 95 %CI 15.1 %–26.9 %).Conclusion In this work, we present a novel AI-based method for measuring colorectal polyp size with significantly higher accuracy than other common sizing methods.